Repurposing HIV Protease Inhibitors Atazanavir and Darunavir as Antifungal Treatments against Candida albicans Infections: An In Vitro and In Vivo Study - Fenley, Juliana de C. [UNESP]; de Barros, Patrícia P. [UNESP]; Carmo, Paulo H. F. do [UNESP]; Garcia, Maíra T. [UNESP]; Rossoni, Rodnei D. [UNESP]; Junqueira, Juliana C. [UNESP] (MDPI, 2022)
Candida albicans is the chief etiological agent of candidiasis, a mycosis prevalent in individuals with acquired immunodeficiency syndrome (AIDS). In recent years, the introduction of human immunodeficiency virus (HIV) protease inhibitors (HIV-PI) has reduced the prevalence of candidiasis in these patients. Seeking new therapeutic strategies based on the perspective of drug repositioning, we evaluated the effects of two second-generation HIV-PIs, atazanavir (ATV) and darunavir (DRV), on virulence factors of C. albicans and experimental candidiasis. For this, clinical strains of C. albicans were subjected to in vitro and in vivo treatments with ATV or DRV. As a result, ATV and DRV exhibited antifungal activity against fungal cells at 512 μg/mL, reduced the viability and biomass of biofilms, and inhibited filamentation of C. albicans. In addition, these HIV-PIs downregulated the expression of SAP2 and BRC1 genes of C. albicans. In an in vivo study, prophylactic use of ATV and DRV prolonged the survival rate of Galleria mellonella larvae infected with C. albicans. Therefore, ATV and DRV showed activity against C. albicans by reducing cell growth, biofilm formation, filamentation, and expression of virulence genes. Furthermore, ATV and DRV decreased experimental candidiasis, suggesting the repurposing of HIV-PIs as antifungal treatments for C. albicans infections.
Keywords: atazanavir sulfate; Candida albicans; darunavir; HIV; protease inhibitors; virulence factors